RESPON PERTUMBUHAN TANAMAN KRISAN POTONG (Chrysanthemum indicum L.) VARIETAS RIRIH TERHADAP DOSIS PUPUK KOTORAN SAPI DAN KONSENTRASI BIOURINE - E. Dwi Sulistya Nugroho; Dian Histifarina; Ardian Elonard (Jurnal Agroekoteknologi, 2019)
ABSTRACTNutrients are an important factor in the cultivation of chrysanthemum cut plants.Availability of nutrients is needed during plant growth and in increasing cropproduction, therefore the addition of nutrients in the form of fertilizer is needed by cut chrysanthemum plants. The use of effective and efficient fertilizers is an indicator in the growth of chrysanthemum cut plants. The purpose of this research was to determine the optimal doses of cattle manure and biourine concentration for the growth of chrysanthemum cut plants. This research was designed with a Randomized Complete Block Design consisting of two factors. The first factor is cattle manure dose which consists of three levels, namely 2 kg per m2 (K1), 3 kg per m2 (K2), and 4 kg per m2 (K3). The second factor is the concentration of biourine which consists of 4 levels, namely 0 ml L-1 of water (B1), 250 ml L-1 of water (B2), 500 ml L-1 of water (B3), and 750 ml L-1 of water (B4). All treatments were repeated 4 times, so that a combination of 48 plots was obtained. Observation parameters included plant height, number ofleaves, stem diameter, leaf length, leaf width, chlorophyll number, flower initiation, flower diameter, flower stem diameter, and flower stalk length. The use of cattle manure at a dose of 2 kg per m2 without the addition of biourine has been able to become the optimal input for the growth of chrysanthemum cut plants.